2021
DOI: 10.3390/insects12040295
|View full text |Cite
|
Sign up to set email alerts
|

Termite Assemblage and Damage on Tree Trunks in Fast-Growing Teak Plantations of Different Age: A Case Study in West Java, Indonesia

Abstract: We conducted surveys of termite assemblages and tree trunks damaged by termites in teakwood (Tectona grandis L.f.) plantations. The surveys were conducted in five-, six-, and nine-year-old plantations. We used a standardized belt-transect to collect termites and build tree inventories. Data of collected termites at the genus and functional-group levels and termites’ diversity between plantations were compared with their attack rate. The results showed that four genera of soil recycler termites belonging to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…robusta had the highest attraction followed by Eucalyptus and Cypress respectively. Fajar et al, (2021), reported that termites foraged on Eucalyptus. Nakabonge & Matovu, (2021) reported that Eucalyptus species are highly susceptible to termites.…”
Section: Evaluation Of Uncrushed Feed Substratesmentioning
confidence: 99%
“…robusta had the highest attraction followed by Eucalyptus and Cypress respectively. Fajar et al, (2021), reported that termites foraged on Eucalyptus. Nakabonge & Matovu, (2021) reported that Eucalyptus species are highly susceptible to termites.…”
Section: Evaluation Of Uncrushed Feed Substratesmentioning
confidence: 99%
“…The relatively high carbon content in lignin compared to cellulose and hemicellulose causes lignin to have a high energy content. Lignin is a complex phenylpropanoid polymer that has a structural role in plant cell walls while providing hydrophobicity and protection against pathogens [31]. The molecular structure of lignin is different when compared to polysaccharides because it consists of an aromatic system composed of phenylpropane units, namely guaiacyl (G) units from trans-coniferyl alcohol precursors, syringyl (S) units from trans-synapyl alcohol precursors, and p-hydroxypenyl (H) of the trans-p-coumaril alcohol precursor [32].…”
Section: Pygcms Of E Pellita Barkmentioning
confidence: 99%
“…Termites are destructive insects that attack trees. The termite genera of Macrotermes, Microtermes, Odontotermes, and Coptotermes frequently attack trees [8,9]. The Coptotermes group's reputation as a significant termite pest in Indonesia was well-known [10].…”
Section: Introductionmentioning
confidence: 99%